Solvent effect on the lower critical solution temperature of biodegradable thermosensitive poly(organophosphazenes) - Lee, SB; Song, SC; Jin, JI; Sohn, YS (SPRINGER-VERLAG, 2000)
The solvent effect on the lower critical solution temperature (LCST) of poly(organophosphazenes) with methoxy-poly(ethyl ene glycol) (MPEG) and amino acid esters as side groups was examined in terms of the structure of polyphosphazenes in aqueous solutions containing one of the organic solvents selected from monoalcohols, ethylene glycol derivatives, alkylamines, and other common solvents. When such a solvent was added to the aqueous solutions of the polymers, their LCST was found to be mainly dependent on the hydrophobic and hydrophilic properties of the solvents. Most of the alcohols and amines with shorter alkyl chains increased the LCST of the polymers but those with longer chains decreased the LCST. Trifluoroethanol (TFE) showed a strong LCST decreasing effect in spite of its short chain, which seems to be due to its strong hydrophobicity. Temperature-induced molecular weight fractionation of the polymer bearing MPEG350 (M-w = 350) and L-aspartic acid ethyl ester as a side group was carried out by using the LCST decreasing effect of TFE, and the fractionated samples were characterized by gel permeation chromatography (GPC) and H-1- and P-31 NMR spectroscopies. Thus it has been shown that a polymer may be fractionated to the higher and lower molecular weight fractions with smaller polydispersity indices (PDI): the polymer with the weight-average molecular weight (M-w) of 73,500 with PDI of 5.56 was fractionated to those of 106,000 with PDI of 4.37 and 11,000 with PDI of 1.86.
Keywords: AMINO-ACID ESTERS; CLOUD-POINT; INORGANIC SALTS; SIDE-GROUPS; POLYMERS; GLYCOL); EXTRACTION; SYSTEM; GEL